Lanthanum-doped cobalt-loaded carbon composite material, preparation method and application thereof, electrochemical sensor and method for detecting carbendazim

The electrochemical sensor modified by mixed cobalt load carbon composite materials solves the problem of inaccurate and low sensitivity in the existing technologies, achieves high sensitivity and selective testing, expands the range of linearity and reduces it. The detection limit.

CN119370902APending Publication Date: 2025-01-28SHIHEZI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411498252.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, when detecting Bacteriaceae, high oxidation potential and low electrochemical activity lead to inaccurate detection and low sensitivity, and low sensor selectivity, making it impossible to effectively identify Bacteriaceae in coexisting substances.

Method used

The mixed cobalt load carbon composite material is used as the working electrode of the electrochemical sensor. The material is prepared through the process of water thermal reaction and thermal solution. It has high adsorption capacity and selectivity, which can effectively improve the sensitivity and selectivity of electrochemical detection.

Benefits of technology

The high -sensitivity and selective testing of the fungal spirit, expanded the linear range of detection to 0.5 to 70.0 μm, reduced the detection limit, and improved the accuracy and efficiency of the detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370902A_ABST
    Figure CN119370902A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of detection and analysis, and particularly relates to a lanthanum-doped cobalt-loaded carbon composite material, a preparation method and application thereof, an electrochemical sensor and a method for detecting carbendazim. The lanthanum-doped cobalt-loaded carbon composite material provided by the invention has high adsorption capacity to carbendazim, so that the lanthanum-doped cobalt-loaded carbon composite material has the characteristic of selectively detecting carbendazim, and is a key for improving the electrochemical detection sensitivity and selectivity. The metal cobalt low-dimensional nano material adopted by the invention has a high-activity surface, a high electron transfer rate and abundant surface vacancies, can effectively improve the efficiency and stability of an electro-catalytic reaction, and particularly has the characteristics of high electrochemical activity, variable valence states, low charge transfer resistance and the like. The lanthanum-doped cobalt-loaded carbon composite material disclosed by the invention has the advantages of large specific surface area, good conductivity, good catalytic performance and the like, meanwhile, the catalytic performance and the conductivity of the composite material are remarkably improved by doping the lanthanum element, the detection sensitivity is improved, and the linear range for detecting carbendazim is relatively wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of detection and analysis, and specifically relates to a lanthanum-doped cobalt-loaded carbon composite material and a preparation method and application thereof, an electrochemical sensor and a method for detecting carbendazim. Background Art

[0002] Carbendazim is a broad-spectrum benzimidazole fungicide and a metabolite of benzoyl. Studies have found that high doses of carbendazim can cause infertility and damage the testicles of experimental animals. Carbendazim residues can cause liver disease and chromosomal aberrations. It is highly toxic to aquatic organisms and has been banned in the United States for use in aquaculture and agricultural industries.

[0003] Based on the characteristics of carbendazim's own electroactivity, there have been many reports on the detection of carbendazim using electrocatalytic methods. However, the high oxidation potential and low electrochemical activity hinder the accurate and sensitive analysis of carbendazim, and the low selectivity of the sensor makes it impossible to identify the target molecule from the coexisting substances.

[0004] At present, in reports on the detection of carbendazim, researchers usually use nanocomposite materials to modify electrodes to solve the problem of selective detection of target analytes. Claudia et al. used hydrogen fluoride as a catalyst and prepared the hybrid material SiO2 / MWCNT by sol-gel method to construct a highly sensitive electrochemical sensor for the detection of carbendazim (CBZ). The glassy carbon electrode modified by this composite material showed good sensitivity and selectivity, with a detection limit of 0.056μM, which can be applied to the detection of CBZ. However, its linear range is only 0.2-4.0μM, and the detection range is narrow. Summary of the invention

[0005] The object of the present invention is to provide a lanthanum-doped cobalt-loaded carbon composite material and its preparation method, application, electrochemical sensor and method for detecting carbendazim. The lanthanum-doped cobalt-loaded carbon composite material provided by the present invention has a wide linear range for detecting carbendazim, and the linear range is 0.5 to 70.0 μM.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The invention provides a lanthanum-doped cobalt-loaded carbon composite material, comprising porous carbon and lanthanum-doped cobalt loaded on the porous carbon; the lanthanum comprises La2O3; and the cobalt is a cobalt oxide low-dimensional nano material.

[0008] Preferably, the molar ratio of the porous carbon to lanthanum is 1-24:1-24.

[0009] Preferably, the molar ratio of lanthanum to cobalt is 1-6:1-6.

[0010] Preferably, the pore size of the lanthanum-doped cobalt-loaded carbon composite material is 2 to 18 nm.

[0011] The present invention also provides a method for preparing the lanthanum-doped cobalt-loaded carbon composite material described in the above scheme, comprising the following steps:

[0012] (1) mixing cobalt salt, 2-methylimidazole and an alcohol solvent, and then performing solid-liquid separation and drying in sequence to obtain a ZIF-67 precursor;

[0013] (2) The ZIF-67 precursor, lanthanum salt, surfactant and alcohol solvent are mixed for hydrothermal reaction and then pyrolyzed to obtain a lanthanum-doped cobalt-loaded carbon composite material.

[0014] Preferably, the temperature of the hydrothermal reaction is 80-200° C., and the insulation reaction time is 2-24 hours.

[0015] Preferably, the pyrolysis is carried out in a protective atmosphere; the pyrolysis includes a heating pyrolysis stage and a heat preservation pyrolysis stage; the heating rate of the heating pyrolysis stage is 2 to 10°C / min; the temperature of the heat preservation pyrolysis stage is 500 to 1000°C, and the heat preservation pyrolysis time is 1 to 5h.

[0016] The present invention also provides the use of the lanthanum-doped cobalt-loaded carbon composite material described in the above scheme or the lanthanum-doped cobalt-loaded carbon composite material obtained by the preparation method described in the above scheme in a carbendazim detection product.

[0017] The present invention also provides an electrochemical sensor, comprising a working electrode, an auxiliary electrode and a reference electrode; the working electrode is a glassy carbon electrode modified with a lanthanum-doped cobalt-loaded carbon composite material; the lanthanum-doped cobalt-loaded carbon composite material is the lanthanum-doped cobalt-loaded carbon composite material described in the above scheme or the lanthanum-doped cobalt-loaded carbon composite material obtained by the preparation method described in the above scheme.

[0018] The present invention also provides a method for detecting carbendazim using the electrochemical sensor described in the above scheme, comprising the following steps:

[0019] The working electrode, reference electrode and auxiliary electrode in the electrochemical sensor described in the above scheme constitute a three-electrode system, and the working electrode is immersed in a carbendazim-PBS standard solution for incubation in the window potential range of 0 to 1.2 V using differential pulse voltammetry or in the window potential range of -0.2 to 0.6 V using square wave voltammetry, and the corresponding current value IP is recorded; an IP-C working curve is drawn with the concentration C of carbendazim as the horizontal axis and the current value IP as the vertical axis; and the IP-C working curve is used to detect carbendazim in the object to be tested.

[0020] The present invention provides a lanthanum-doped cobalt-loaded carbon composite material. The lanthanum-doped cobalt-loaded carbon composite material provided by the present invention has a high adsorption capacity for carbendazim, so that it has the characteristic of selectively detecting carbendazim, which is the key to improving the sensitivity and selectivity of electrochemical detection. The metal cobalt low-dimensional nanomaterial used in the present invention has a highly active surface, an efficient electron transfer rate and abundant surface vacancies, which can effectively improve the efficiency and stability of the electrocatalytic reaction, and especially has the characteristics of high electrochemical activity, variable valence state and low charge transfer resistance. The lanthanum-doped cobalt-loaded carbon composite material of the present invention has the advantages of large specific surface area, good electrical conductivity and good catalytic performance. At the same time, the lanthanum element doping significantly improves the catalytic performance and electrical conductivity of the composite material, further improves the sensitivity of detection, and has a wide linear range for detecting carbendazim, and the linear range is 0.5.0~70.0μM.

[0021] The present invention also provides a method for preparing the lanthanum-doped cobalt-loaded carbon composite material described in the above scheme. ZIFs is a zeolite imidazole framework formed by the interaction of MOF and metal ions, wherein 2-methylimidazole cobalt (ZIF-67) has high catalytic activity, good thermochemical stability, adjustable pore size, and is rich in a large number of unsaturated metal sites. The present invention converts ZIFs into nanomaterials such as metal oxides by pyrolysis, and introduces another metal ion during the pyrolysis process, which can significantly improve its electrical conductivity and structural stability, so that the electrochemical sensor prepared by the La2O3-Co / C composite material of the present invention has a wide linear range of 1.0 to 70.0 μM, and has high catalytic performance and high sensitivity, and low cost.

[0022] The present invention also provides the use of the lanthanum-doped cobalt-loaded carbon composite material described in the above scheme or the lanthanum-doped cobalt-loaded carbon composite material obtained by the preparation method described in the above scheme in a carbendazim detection product. The lanthanum-doped cobalt-loaded carbon composite material provided by the present invention can be used to detect carbendazim and has a wide linear range of 1.0 to 70.0 μM.

[0023] The present invention also provides an electrochemical sensor. The present invention uses a glassy carbon electrode modified by a lanthanum-doped cobalt-loaded carbon composite material as a working electrode to construct an electrochemical sensor capable of rapid, efficient and sensitive detection of carbendazim, and the electrochemical oxidation process on the sensor involves 2 protons and 2 electrons. The electrochemical sensor of the present invention has a wide linear range of 1.0 to 70.0 μM, and the minimum detection limit for carbendazim is 0.167 μM. It can realize rapid and sensitive detection of carbendazim, meet detection needs, and has the advantages of simple sample pretreatment, high detection sensitivity and short analysis time.

[0024] The present invention also provides a method for detecting carbendazim using the electrochemical sensor described in the above scheme. The electrochemical sensor provided by the present invention can detect carbendazim with high efficiency and sensitivity, and is easy to operate and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 This is a scanning electron microscope image of the lanthanum-doped cobalt-supported carbon composite material prepared in Example 1;

[0027] Figure 2 The differential pulse voltammetry curves of glassy carbon electrode, ZIF-67@La / GCE, and La2O3-Co / C / GCE in 50 μM carbendazim solution;

[0028] Figure 3 Electrochemical impedance spectroscopy of glassy carbon electrode, ZIF-67@La / GCE, and La2O3-Co / C / GCE in probe solution;

[0029] Figure 4 This is a differential pulse voltammetry curve obtained in Example 2;

[0030] Figure 5-6 This is the standard working curve for carbendazim detection obtained in Example 2. DETAILED DESCRIPTION

[0031] The invention provides a lanthanum-doped cobalt-loaded carbon composite material, comprising porous carbon and lanthanum-doped cobalt loaded on the porous carbon; the lanthanum comprises La2O3; and the cobalt is a cobalt oxide low-dimensional nano material.

[0032] In the present invention, the amount ratio of the porous carbon to lanthanum is preferably 1-24:1-24, specifically 24:1, 20:1, 16:1, 12:1, 8:1, 4:1, 1:1, 1:4, 1:8, 1:12, 1:16, 1:20 or 1:24.

[0033] In the present invention, the molar ratio of lanthanum to cobalt is preferably 1-6:1-6, specifically 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5 or 1:6.

[0034] In the present invention, the pore size of the lanthanum-doped cobalt-loaded carbon composite material is preferably 2 to 18 nm, specifically 2 nm, 3.7 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm or 18 nm.

[0035] The present invention also provides a method for preparing the lanthanum-doped cobalt-loaded carbon composite material described in the above scheme, comprising the following steps:

[0036] (1) mixing cobalt salt, 2-methylimidazole and an alcohol solvent, and then performing solid-liquid separation and drying in sequence to obtain a ZIF-67 precursor;

[0037] (2) The ZIF-67 precursor, lanthanum salt, surfactant and alcohol solvent are mixed for hydrothermal reaction and then pyrolyzed to obtain a lanthanum-doped cobalt-loaded carbon composite material.

[0038] The present invention mixes cobalt salt, 2-methylimidazole and an alcohol solvent (referred to as the first alcohol solvent) (referred to as the first mixture), and then sequentially performs solid-liquid separation and drying to obtain a ZIF-67 precursor. In the present invention, the cobalt salt is preferably cobalt nitrate; and the cobalt nitrate is preferably Co(NO3)3·6H2O.

[0039] In the present invention, the molar ratio of the cobalt salt to 2-methylimidazole is preferably 1-4:1-8, specifically 4:1, 3:1, 2:1, 3:2, 1:1, 2:3, 1:2, 2:5, 1:3, 2:7, 1:4, 1:6 or 1:8.

[0040] In the present invention, the first alcohol solvent is preferably methanol.

[0041] In the present invention, the ratio of the total amount of the cobalt salt and 2-methylimidazole to the amount of the first alcohol solvent is preferably 1:13-132, specifically 1:13, 1:20, 1:50, 1:80, 1:100, 1:120, 1:130 or 1:132.

[0042] In the present invention, the first mixing is preferably stirring; after the first mixing, the obtained mixture is preferably allowed to stand; the standing time is preferably 6 to 24 hours, specifically 6 hours, 10 hours, 14 hours, 18 hours, 22 hours or 24 hours.

[0043] In the present invention, the solid-liquid separation is preferably centrifugation; the centrifugal rotation speed is preferably 7000-10000rpm, specifically 7000rpm, 8000rpm, 9000rpm or 10000rpm, and the centrifugal time is preferably 6-20min, specifically 6min, 10min, 15min or 20min.

[0044] In the present invention, the drying is preferably oven drying; the drying temperature is preferably 30-65°C, specifically 30°C, 35°C, 45°C, 55°C or 65°C, and the heat preservation and drying time is preferably 12-24h, specifically 12h, 15h, 18h, 21h or 24h.

[0045] After obtaining the ZIF-67 precursor, the present invention mixes the ZIF-67 precursor, lanthanum salt, surfactant and alcohol solvent (referred to as the second alcohol solvent) (referred to as the second mixture to obtain a dispersion) for hydrothermal reaction and then pyrolysis to obtain a lanthanum-doped cobalt-loaded carbon composite material. In the present invention, the lanthanum salt is preferably La(NO3)3·6H2O.

[0046] In the present invention, the ratio of the ZIF-67 precursor to the lanthanum salt is preferably 1-6:1-6, specifically 6:1, 5:1, 4:1, 3:1, 5:2, 2:1, 5:3, 3:2, 4:3, 5:4, 6:5, 1:1, 4:5, 3:4, 2:3, 3:5, 1:2, 2:5, 1:3, 1:4, 1:5, 1:6.

[0047] In the present invention, the surfactant is preferably a quaternary ammonium salt; the quaternary ammonium salt is preferably cetyltrimethylammonium bromide (CTAB).

[0048] In the present invention, the molar ratio of the ZIF-67 precursor to the surfactant is preferably 1-5:1-5, specifically 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4 or 1:5.

[0049] In the present invention, the second alcohol solvent is preferably ethanol.

[0050] In the present invention, the concentration of the surfactant in the dispersion is preferably 1-10 mM, specifically 1 mM, 3 mM, 5 mM, 7 mM or 10 mM.

[0051] In the present invention, the second mixing is preferably ultrasonic mixing; the power of the ultrasonic mixing is preferably 100 W, and the frequency is preferably 40 kHz.

[0052] In the present invention, the temperature of the hydrothermal reaction is preferably 80-200°C, specifically 80°C, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, the insulation reaction time is preferably 2-24h, specifically 2h, 4h, 8h, 12h, 16h, 20h or 24h; the equipment for the hydrothermal reaction is preferably a polytetrafluoroethylene reactor. The present invention obtains a ZIF-67@La (ZIF-67 loaded with La) composite material through a hydrothermal reaction.

[0053] In the present invention, after the hydrothermal reaction, the obtained reaction product is preferably washed, solid-liquid separated and dried in sequence; the washing reagent is preferably ethanol; the number of washings is preferably more than 3 times; the solid-liquid separation is preferably centrifugation; the centrifugation speed is preferably 8000 rpm, and the centrifugation time is preferably 5 min; the drying is preferably oven drying; the oven drying temperature is preferably 60°C, and the drying time is preferably 12 h.

[0054] In the present invention, the pyrolysis is preferably carried out in a protective atmosphere; the protective atmosphere is preferably nitrogen; the pyrolysis equipment is preferably a tubular furnace; the pyrolysis preferably includes a heating pyrolysis stage and a heat preservation pyrolysis stage; the heating rate of the heating pyrolysis stage is preferably 2-10°C / min, specifically 2°C / min, 5°C / min, 8°C / min or 10°C / min; the temperature of the heat preservation pyrolysis stage is preferably 500-1000°C, specifically 500°C, 600°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C, and the heat preservation pyrolysis time is preferably 1-5h, specifically 1h, 2h, 3h, 4h or 5h. The present invention pyrolyzes ZIF-67@La into La2O3-Co / C by pyrolysis.

[0055] In the present invention, after the pyrolysis, the process preferably further comprises allowing the obtained product to stand to room temperature.

[0056] The present invention also provides the use of the lanthanum-doped cobalt-loaded carbon composite material described in the above scheme or the lanthanum-doped cobalt-loaded carbon composite material obtained by the preparation method described in the above scheme in a carbendazim detection product.

[0057] The present invention also provides an electrochemical sensor, comprising a working electrode, an auxiliary electrode and a reference electrode; the working electrode is a glassy carbon electrode modified with a lanthanum-doped cobalt-loaded carbon composite material; the lanthanum-doped cobalt-loaded carbon composite material is the lanthanum-doped cobalt-loaded carbon composite material described in the above scheme or the lanthanum-doped cobalt-loaded carbon composite material obtained by the preparation method described in the above scheme.

[0058] In the present invention, the working electrode (referred to as La2O3-Co / C / GCE electrode) is preferably prepared by applying dispersed droplets of lanthanum-doped cobalt-loaded carbon composite material to the surface of the glassy carbon electrode and then drying.

[0059] In the present invention, the concentration of the lanthanum-doped cobalt-loaded carbon composite material dispersion is preferably 1 to 20 mg / mL, specifically 1 mg / mL, 5 mg / mL, 10 mg / mL, 15 mg / mL or 20 mg / mL; the preparation method of the lanthanum-doped cobalt-loaded carbon composite material dispersion is preferably: mixing the lanthanum-doped cobalt-loaded carbon composite material and N,N-dimethylformamide (DMF); the mixing is preferably ultrasonic mixing.

[0060] In the present invention, the drop coating amount is preferably 0.079 to 0.800 μL / mm 2 The drip coating device is preferably a pipette gun; the drying is preferably infrared lamp drying or air drying. The present invention evaporates the solvent by drying to form a uniform lanthanum-doped cobalt-loaded carbon composite material film on the surface of the working electrode.

[0061] In the present invention, the glassy carbon electrode is preferably pre-treated before use; the pre-treatment is preferably polishing and drying in sequence; the polishing is preferably: the glassy carbon electrode is polished and then washed with water for the first time, washed with alcohol, and washed with water again in sequence; the polishing is preferably polished into a mirror surface using aluminum oxide polishing powder; the water used for the first water wash is preferably distilled water; the alcohol used for the alcohol wash is preferably anhydrous ethanol; the water used for the second water wash is preferably distilled water; the first water wash, alcohol wash, and second water wash are independently preferably ultrasonic cleaning, and the cleaning time is independently preferably 5 minutes; the drying is preferably drying with an infrared lamp. The present invention completely removes aluminum oxide powder and other contaminants adsorbed on the surface of the glassy carbon electrode through polishing.

[0062] In the present invention, the auxiliary electrode is preferably a platinum electrode.

[0063] In the present invention, the reference electrode is preferably a saturated calomel electrode.

[0064] The present invention also provides a method for detecting carbendazim using the electrochemical sensor described in the above scheme, comprising the following steps:

[0065] The working electrode, the reference electrode and the auxiliary electrode in the electrochemical sensor constitute a three-electrode system, and the working electrode is immersed in a carbendazim-PBS standard solution for incubation in the window potential range of 0 to 1.2 V by differential pulse voltammetry or in the window potential range of -0.2 to 0.6 V by square wave voltammetry, and the corresponding current value IP is recorded; an IP-C working curve is drawn with the concentration C of carbendazim as the horizontal coordinate and the current value IP as the vertical coordinate; and the IP-C working curve is used to detect carbendazim on the object to be tested.

[0066] In the present invention, the carbendazim-PBS standard solution is a carbendazim standard solution prepared using PBS solution; the concentration of the PBS solution is preferably 0.1M, and the pH value is preferably 6.0; the concentration of carbendazim in the carbendazim-PBS standard solution is preferably 0.5-70μM, specifically 0.5μM, 1μM, 5μM, 10μM, 30μM, 50μM or 70μM.

[0067] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0068] In the specific embodiments of the present invention, the specific experimental conditions not specified are carried out according to conventional conditions or conditions recommended by the reagent company; unless otherwise specified, the reagents and consumables used are all commercially available products.

[0069] Example 1

[0070] (1) 2.1825 g of Co(NO3)3·6H2O, 2.46 g of 2-methylimidazole and 100 mL of methanol were stirred and mixed, and then allowed to stand for 12 h, centrifuged (speed: 8000 rpm, time: 7 min), and dried (temperature: 60°C, time: 12 h). The molar ratio of Co(NO3)3·6H2O to 2-methylimidazole was 1:4, and the volume of methanol was 100 mL, to obtain a ZIF-67 precursor.

[0071] (2) 0.2 g of ZIF-67, 0.13 g of La(NO3)3·6H2O and 0.1094 g of CTAB were dispersed in 60 mL of ethanol and ultrasonicated for 15 min (power 100 W, frequency 40 kHz) to obtain a mixed dispersion. The mixed dispersion was placed in a polytetrafluoroethylene reactor for hydrothermal reaction. After reacting at 160°C for 8 h, the product was washed 3 times with ethanol and collected by centrifugation (8000 rpm, 5 min), and dried at 60°C for 12 h to obtain a ZIF-67@La composite material.

[0072] (3) The ZIF-67@La composite material was placed in a tubular furnace filled with nitrogen, heated to 700°C at a rate of 5°C / min, thermally decomposed for 2 hours, and allowed to stand to room temperature to obtain a lanthanum-doped cobalt-loaded carbon composite material.

[0073] (4) Before modifying the electrode, the glassy carbon electrode (GCE) was polished to a mirror surface with 0.05 μm alumina powder, and then the glassy carbon electrode was ultrasonically cleaned with distilled water, anhydrous ethanol, and distilled water for 5 min in sequence, and dried in air; the lanthanum-doped cobalt-loaded carbon composite material was dispersed in DMF to obtain a lanthanum-doped cobalt-loaded carbon composite material dispersion with a concentration of 5 mg / mL; 3 μL of the lanthanum-doped cobalt-loaded carbon composite material dispersion was drop-coated on the surface of GCE and dried (50°C, 5 min) to obtain an electrochemical sensor (denoted as La2O3-Co / C / GCE).

[0074] (5) Repeat step (4), except that the lanthanum-doped cobalt-loaded carbon composite material is replaced by the ZIF-67@La composite material to obtain a control electrochemical sensor (denoted as ZIF-67@La / GCE).

[0075] The lanthanum-doped cobalt-loaded carbon composite material prepared in this example was examined by SEM, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the lanthanum-doped cobalt-loaded carbon composite material provided by the present invention presents collapsed rhombic dodecahedrons with filamentous crystals on the surface, and these rhombic dodecahedrons are irregularly agglomerated to present irregular agglomerates, and there are filamentous crystals on the surface of the irregular agglomerates, which proves the successful doping of La; the lanthanum-doped cobalt-loaded carbon composite material provided by the present invention can promote the transfer of carbendazim electrons and promote the oxidation of carbendazim on the modified electrode.

[0076] Differential pulse voltammetry (DPV) analysis was performed on the glassy carbon electrode, ZIF-67@La / GCE, and La2O3-Co / C / GCE in a 50 μM carbendazim solution. The results are shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the La2O3-Co / C / GCE sensor has the highest response value and the best performance.

[0077] Electrochemical impedance spectroscopy (EIS) analysis was performed on the glassy carbon electrode, ZIF-67@La / GCE, and La2O3-Co / C / GCE in the probe solution. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that La2O3-Co / C has a large specific surface area and the smallest resistance to electron transfer, so it has the best conductivity and catalytic properties.

[0078] Example 2 Detection of carbendazim concentration

[0079] In a phosphate buffer solution (pH=3.0) containing different concentrations of carbendazim (0.5 μM, 1 μM, 5 μM, 10 μM, 20 μM, 30 μM, 40 μM, 50 μM, 60 μM and 70 μM), the electrochemical sensor prepared in Example 1 was connected to a test circuit, and the concentration of thiabendazim was measured by differential pulse voltammetry. The concentration of thiabendazim was used as the horizontal axis (in μM) and the oxidation peak current value was used as the vertical axis (in μA). A standard curve was established: y=0.1632+0.7549x(R 2 =0.9941), the differential pulse voltammetry curve is as follows Figure 4 The standard curve is shown in Figures 5-6 shown. Figure 5 and Figure 6 The concentration is calculated by chronoamperometry and then a linear line is drawn corresponding to the current, as well as a linear line of lg concentration and current.

[0080] according to Figure 4 It can be seen that the electrochemical sensor of the present invention has a good linear relationship (R 2=0.9941), and has a wide linear range (0.5-70.0 μM) and a low detection limit (0.167 μM), which fully demonstrates that the lanthanum-doped cobalt-loaded carbon composite material of the present invention can successfully detect unknown concentrations of carbendazim, further improving the detection accuracy.

[0081] Example 3 Quantitative rapid detection of carbendazim in actual samples

[0082] In order to determine the application performance of the electrochemical sensor of the present invention in practice, the electrochemical sensor of Example 1 was used to detect the concentration of carbendazim in the grinding liquid of pear peel and apple peel: 2.0g sample (pear peel or apple peel) was added with 3.0g anhydrous sodium sulfate and mashed, 10mL ethanol was added, and the mixture was shaken (150 times / min, 2min), ultrasonicated (150W, 40kHz, 10min), and centrifuged (7000rpm, 8min) in sequence, and the supernatant was taken. The sample residue was then added with 10mL ethanol for secondary extraction, and the above two supernatants were combined in a 25mL volumetric flask and fixed to volume with ethanol. 10mL actual sample ethanol solution was taken and mixed with PBS solution with pH value = 6.0 to prepare carbendazim detection solution of different concentrations, and the carbendazim solution was detected by DPV, and the peak current value was substituted into the linear equation to obtain the average concentration, thereby calculating the recovery rate of carbendazim, and the results are shown in Table 1.

[0083] Table 1 Recovery and RSD of carbendazim

[0084]

[0085] It can be seen from Table 1 that the recovery rate of the electrochemical sensor of the present invention through electrochemical detection of carbendazim is 91.3-99.9%, and the RSD is not higher than 3.52%, indicating that the electrochemical sensor provided by the present invention can be used for the actual detection of carbendazim.

[0086] It can be seen from the above examples that the electrochemical sensor provided by the present invention can not only successfully detect carbendazim, but also has the characteristics of high sensitivity, rapid detection and good stability, and can be used for the determination of the content of carbendazim.

[0087] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A lanthanum-doped cobalt-loaded carbon composite material, characterized in that: comprising porous carbon and lanthanum-doped cobalt supported on the porous carbon; The lanthanum includes La2O3; The cobalt is a cobalt oxide low-dimensional nano material.

2. The lanthanum-doped cobalt-loaded carbon composite material according to claim 1, characterized in that: The amount ratio of the porous carbon to lanthanum is 1-24:1-24.

3. The lanthanum-doped cobalt-loaded carbon composite material according to claim 1 or 2, characterized in that: The molar ratio of lanthanum to cobalt is 1-6:1-6.

4. The lanthanum-doped cobalt-loaded carbon composite material according to claim 1, characterized in that: The pore size of the lanthanum-doped cobalt-loaded carbon composite material is 2-18 nm.

5. The method for preparing the lanthanum-doped cobalt-supported carbon composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing cobalt salt, 2-methylimidazole and an alcohol solvent, and then performing solid-liquid separation and drying in sequence to obtain a ZIF-67 precursor; (2) The ZIF-67 precursor, lanthanum salt, surfactant and alcohol solvent are mixed for hydrothermal reaction and then pyrolyzed to obtain a lanthanum-doped cobalt-loaded carbon composite material.

6. The preparation method according to claim 5, characterized in that: The temperature of the hydrothermal reaction is 80-200° C., and the insulation reaction time is 2-24 hours.

7. The preparation method according to claim 5 or 6, characterized in that: The pyrolysis is carried out in a protective atmosphere; The pyrolysis comprises a temperature-raising pyrolysis stage and a temperature-keeping pyrolysis stage; The heating rate of the heating pyrolysis stage is 2 to 10°C / min; The temperature of the heat preservation pyrolysis stage is 500-1000° C., and the heat preservation pyrolysis time is 1-5 hours.

8. Use of the lanthanum-doped cobalt-loaded carbon composite material according to any one of claims 1 to 4 or the lanthanum-doped cobalt-loaded carbon composite material obtained by the preparation method according to any one of claims 5 to 7 in a carbendazim detection product.

9. An electrochemical sensor, characterized in that: It includes working electrode, auxiliary electrode and reference electrode; The working electrode is a glassy carbon electrode modified by a lanthanum-doped cobalt-loaded carbon composite material; The lanthanum-doped cobalt-supported carbon composite material is the lanthanum-doped cobalt-supported carbon composite material according to any one of claims 1 to 4 or the lanthanum-doped cobalt-supported carbon composite material obtained by the preparation method according to any one of claims 5 to 7.

10. A method for detecting carbendazim using the electrochemical sensor according to claim 9, characterized in that: The following steps are involved: The working electrode, reference electrode and auxiliary electrode in the electrochemical sensor of claim 9 constitute a three-electrode system, and the working electrode is immersed in a carbendazim-PBS standard solution for incubation in the window potential range of 0 to 1.2 V using differential pulse voltammetry or in the window potential range of -0.2 to 0.6 V using square wave voltammetry, and the corresponding current value IP is recorded; With the concentration C of carbendazim as the horizontal axis and the current value IP as the vertical axis, the IP-C working curve is drawn; The IP-C working curve is used to detect carbendazim on the test object.